Fucoidan from Ascophyllum nodosum Suppresses Postprandial Hyperglycemia by Inhibiting Na+/Glucose Cotransporter 1 Activity - Xindi Shan; Xueliang Wang; Hao Jiang; Chao Cai; Jiejie Hao; Guangli Yu (Marine Drugs, 2020)
We previously demonstrated that fucoidan with a type II structure inhibited postprandial hyperglycemia by suppressing glucose uptake, but the mechanism remains elusive. Here, we aimed to assess whether the effect of glucose absorption inhibition was related to the basic structure of fucoidans and preliminarily clarified the underlying mechanism. Fucoidans with type II structure and type I structure were prepared from Ascophyllumnodosum (AnF) or Laminariajaponica (LjF) and Kjellmaniellacrassifolia (KcF), respectively. The effects of various fucoidans on suppressing postprandial hyperglycemia were investigated using in vitro (Caco-2 monolayer model), semi-in vivo (everted gut sac model), and in vivo (oral glucose tolerance test, OGTT) assays. The results showed that only AnF with a type II structure, but not LjF or KcF with type I structure, could inhibit the glucose transport in the Caco-2 monolayer and everted gut sac models. A similar result was seen in the OGTT of Kunming mice and leptin receptor-deficient (db/db) mice, where only AnF could effectively inhibit glucose transport into the bloodstream. Furthermore, AnF (400 mg/kg/d) treatment decreased the fasting blood glucose, HbA1c, and fasting insulin levels, while increasing the serum glucagon-like peptide-1 (GLP-1) level in obese leptin receptor-deficient (db/db) mice. Furthermore, surface plasmon resonance (SPR) analysis revealed the specific binding of AnF to Na+/glucose cotransporter 1 (SGLT1), which indicated the effect of AnF on postprandial hyperglycemia could be due to its suppression on SGLT1 activity. Taken together, this study suggests that AnF with a type II structure can be a promising candidate for hyperglycemia treatment.